A novel approach in the management of mandibular degree II furcation defects using bone grafts in conjunction with a biomimetic agent: A randomized controlled clinical trial - Koyyalamudi Prudhvi; Katragadda Raja Venkatesh Murthy (Wolters Kluwer Medknow Publications, 2020)
Aim: Of the periodontal defects requiring regeneration, degree II furcation defects pose a substantial challenge to clinicians. This study was designed to evaluate the relative effectiveness of bone autograft (BA) and autologous platelet-rich fibrin (PRF) as against decalcified freeze-dried bone allograft (DFDBA) along with autologous PRF in the management of degree II mandibular furcation defects.Materials and Methods: Fourteen patients (11 men and 3 women; mean age: 42.36 years), with bilateral degree II buccal furcation defects in the mandibular molars, were enrolled in the study. In each patient, randomly selected sites were divided into control site (site A) which received BA with PRF membrane and test site (site B) received DFDBA + PRF mixed with graft and also as a membrane using split-mouth design. Clinical parameters including plaque index, gingival index, gingival marginal levels, probing depth, and clinical attachment level were recorded at baseline and at 3 and 6 months' postsurgery. Horizontal and vertical furcation measurements were taken prior to the surgery through sounding and after degranulation. These measurements were repeated after 6 months. Results: The mean reduction in the horizontal defect depth was 1.86 ± 0.66 mm (70.75%) in site A and 1.71 ± 0.73 mm (74.25%) in site B. The mean improvement in the vertical defect fill was 1.64 ± 0.74 mm (55.8%) in site A and 1.43 ± 1.34 mm (64.86%) in site B was achieved. Conclusion: The use of combination therapy using either BA or DFDBA in conjunction with PRF appears to be effective in treating furcations.